2014
DOI: 10.1016/j.rmed.2013.10.007
|View full text |Cite
|
Sign up to set email alerts
|

Nocturnal noninvasive positive pressure ventilation in stable COPD: A systematic review and individual patient data meta-analysis

Abstract: At present, there is insufficient evidence to support the application of routine NIPPV in patients with stable COPD. However, higher IPAP levels, better compliance and higher baseline PaCO2 seem to improve PaCO2.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
103
0
9

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 133 publications
(117 citation statements)
references
References 37 publications
(64 reference statements)
5
103
0
9
Order By: Relevance
“…In a recent meta-analysis based on individual data, it was also shown that patients who were more hypercapnic at baseline (PaCO2 >55 mm Hg) showed more reduction in their daytime PaCO2 compared with patients who were less hypercapnic 11 . Monitoring seems to be more important to confirm whether ventilation was effective or not than the type of ventilation.…”
Section: Adequacy Of Ventilatory Support During Sleepmentioning
confidence: 99%
See 2 more Smart Citations
“…In a recent meta-analysis based on individual data, it was also shown that patients who were more hypercapnic at baseline (PaCO2 >55 mm Hg) showed more reduction in their daytime PaCO2 compared with patients who were less hypercapnic 11 . Monitoring seems to be more important to confirm whether ventilation was effective or not than the type of ventilation.…”
Section: Adequacy Of Ventilatory Support During Sleepmentioning
confidence: 99%
“…This metaanalysis showed that 3 months of NIPPV in patients with stable COPD did not improve lung function, gas exchange, sleep efficiency, or 6-minute walking distance. [11,12] Casanova and colleagues studied the effects of longterm NIPPV (a duration of 12 months) to either NIPPV plus standard care or to standard care alone. The number of hospital admissions was lower after 3 months (5% vs 15%).…”
Section: Uncontrolled Trialsmentioning
confidence: 99%
See 1 more Smart Citation
“…Global Initiative for Chronic Obstructive Lung Disease -GOLD) ne daje preporuke vezane uz dugotrajnu primjenu NIV-a kod ove subpopulacije bolesnika. [13][14][15] Kombinacija NIV-a s dugotrajnim liječenjem kisikom mogla bi biti korisna samo u pojedinih bolesnika s KOPB-om i naglašenom dnevnom hiperkapnijom. 16 Za razliku od toga, jasno su dokazani pozitivni učinci primjene kontinuiranoga pozitivnog tlaka zraka u dišnim putovima (engl.…”
Section: Opstruktivne Plućne Bolestiunclassified
“…68 Interestingly, the most recent meta-analysis concluded that insufficient evidence is available to support the use of routine NIV in subjects with stable COPD, but that higher IPAPs, better adherence, and higher baseline P aCO 2 seem to impact improvements in physiology. 69 Obviously, ventilator settings play a predominant role when deciding whether NIV is beneficial in stable hypercapnic COPD.…”
Section: High-intensity Niv In Copdmentioning
confidence: 99%